1984
DOI: 10.1300/j013v09n01_05
|View full text |Cite
|
Sign up to set email alerts
|

Work Disability from Coronary Heart Disease in Women

Abstract: This study investigates the comparatively high rate of work disability from coronary disease in women. A sample of working women and men hospitalized for acute myocardial infarction was followed for two years to ascertain patterns of labor market withdrawal. Women were more likely than men at 24 months to have withdrawn entirely from market work. Multivariate statistical analysis suggests this greater likelihood stems from differences in behavioral responses to disease rather than from differences in disease s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Such issues may not hold the same significance for females. For example, Chirikos and Nickel (1984) found that women were more likely to withdraw from work following a cardiac episode that was thought to be because of financial inducements not being considered strong enough for them to stay at work.…”
Section: Discussionmentioning
confidence: 99%
“…Such issues may not hold the same significance for females. For example, Chirikos and Nickel (1984) found that women were more likely to withdraw from work following a cardiac episode that was thought to be because of financial inducements not being considered strong enough for them to stay at work.…”
Section: Discussionmentioning
confidence: 99%
“…With advancing age, the risk of CHD is more equal between sexes, and the greater survival of women in most industrialized populations means that the number of women with CHD may even surpass that in men in old age [26]. Women with angina pectoris and MI have been found to be at higher risk for diminished functional capacity and work disability compared to men [27,28]. A recent prospective study concerning gender-specific changes in quality of life following cardiovascular disease [29] showed that premorbid physical functioning in women was no better than that of men after the disease event, and physical functioning deteriorated markedly after the onset of disease, in both women and men.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, a broad con-R WOMEN 6 HEALTH clusion that the processes of causation and selection for roles and health are always similar for men and women is not warranted. Other research suggests that social selection does differ (women with serious health problems abandon employment more rapidly than comparable men (Chirikos and Nickel, 1984; but see also Brown and Rawlinson, 1977). We suspect there are more similarities than differences in the processes, but that is a hypothesis which needs more testing.…”
Section: Are Role Burden Effects On Health the Same For Women And Men?mentioning
confidence: 83%